ChemInform Abstract: Iron‐Catalyzed Arene Alkylation Reactions with Unactivated Secondary Alcohols. Issue 37 (16th September 2014) - Jefferies, Latisha R.; Cook, Silas P.
Abstract This methodology facilitates the synthesis of phenacyl butenoic acid (IV) which exhibit antiproliferative activities.